A Study of Capital Structure of Indian Power Generation and Supply Firms: Unbalanced Panel Data - Tupe, Sanjay (Asian Development Policy Review, 2020)
This paper reveals the determinants of capital structure of power generation and supply firms (PGSFs) in India for the period 1993-2004 using unbalanced panel data. We try for several estimation methods of panel data, random effects estimation technique is selected after using specification tests. The results are similar with earlier studies relating to traditional determinants of capital structure like tangibility, profitability, however signs of variables: size, growth opportunities, cost of borrowing, and liquidity in the firm effects and firm and time effects are correct but not significant. Among the macro-economic variables, inflation and bank development are significantly related with leverage of PGSFs. The findings from the unbalanced panel data model reveal presence of major theories of finance in the case of Indian PGSFs. Further study suggests, focus should be on designing pro-bank and stock market finance policies to overcome the problems faced by PGSFs. This study proposes to offer special treatment to individual and institutional taxpayers in tax rebate for increasing investment in the equity and bonds of PGSFs.